Maintaining Harmonization In Preventing Potential Social-Religious Conflicts In The City of Semarang Through Community Pluralism Education - Sri Suneki; Mahmud Yunus; Haryono Haryono (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
One of the challenges and threats for religious communities today is the existence of religious fundamentalists who are trying to replace the Pancasila ideology. Apart from that, the diverse lives of the people of Semarang City intersect with differences in ethnicity, race, and culture, which can also cause social conflict. Research on mapping potential social conflict using a pluralism-based community social education approach has an urgency to be carried out to avoid social conflict. This research aims to analyze the mapping of potential social conflict in Semarang City with community social education based on pluralism education. This qualitative research uses a case study approach. Data collection techniques use observation at the research location, documentation with supporting literature, and in-depth interviews with informants. Researchers tested the validity of the data using source triangulation and technique triangulation. The research results show that community social education is one of the strategies that can be used to maintain harmony in the city of Semarang and prevent socio-religious conflict.